The DSM and Professional Practice: Research, Clinical, and Institutional Perspectives. (June 2016) - Halpin, Michael
How mental illnesses are defined has significant ramifications, given the substantial social and individual repercussions of these conditions. Using actor–network theory, I analyze how mental health professionals use the Diagnostic and Statistical Manual of Mental Disorders ( DSM ) in their work. Drawing on observations of a neuropsychological laboratory and interviews with 27 professionals (i.e., psychiatrists, psychologists), I investigate how the DSM is used in research, clinical, and institutional work. In research, the DSM influences study design and exclusion/inclusion criteria. In the clinic, the DSM influences how disorders are conceptualized and diagnosed. Institutionally, the DSM aligns the patient–professional encounter to insurance and pharmaceutical interests. I conclude that the DSM operates as multiple, context-specific taxonomies that pervasively influence professional practices, such that all possible actions must orient to DSM criteria, with professionals both a source and an object of institutionalized gaze.